Challenging the US Supreme Court's Majority Ruling on Roe v. Wade at the International Human Rights Level - Marge Berer (Harvard FXB Center for Health and Human Rights, 2023)
This paper proposes that US human rights experts and abortion rights advocates challenge the striking down of Roe v. Wade in June 2022 by the majority of US Supreme Court justices because of the multiple human rights violations it has engendered. The paper has three parts. The first part summarizes the compelling response of the three dissenting Supreme Court justices to the majority ruling, which spells out those violations in detail. The second part offers a history of cases of violations of human rights related to abortion in other countries that have been heard and adjudicated by a range of human rights bodies in the last 20 years, and their outcomes. It shows that working on these cases has created working relationships between national and international human rights experts and advocates. Based on this information, the third part proposes that US human rights and abortion rights advocates take a case to the Inter-American Commission on Human Rights against the US Supreme Court ruling, asking the commission to direct the US government to void the majority ruling on Roe v. Wade-on the grounds that it violates the human rights of anyone who seeks an abortion and potentially also of those whose wanted pregnancies become a risk to their health and life and need to be terminated. And if the United States does not agree, the commission should refer the case to the Inter-American Court of Human Rights.